Desain Signsystem Toilet untuk Pengembangan Brand - Miyosa, Atmaja Septa (Jurnal Ilmiah Multimedia dan Komunikasi, 2018)
Brand development built to strengthen the public memory of an information on a brand. Strategies undertaken by designers include exploring the visual strength attached to the brand. The result of effective visual exploration is the creation of a sign, because the sign is a visual object that is directly visible to the public. Signs that have a chance to be processed in aesthetic and communicative is a signsystem of toilet. Signsystem in the Recheese Factory uses the symbol of cheese, De Tjolomadoe uses the symbol of landmark, Bali Safari Marine Park uses tribal and craft symbols, Museum Tubuh Jatimpark1 uses biological symbols and illustrations of cartoon.